Effect of Operational Variables on Supercritical Foaming of Caffeic Acid-Loaded Poly(Lactic Acid)/Poly(Butylene Adipate-Co-Terephthalate) Blends for the Development of Sustainable Materials - Rodriguez-Mercado, F; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A; Rivera-Fuentealba, P (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Expanded polystyrene will account for 5.3% of total global plastic production in 2021 and is widely used for food packaging due to its excellent moisture resistance and thermal insulation. However, some of these packages are often used only once before being discarded, generating large amounts of environmentally harmful plastic waste. A very attractive alternative to the conventional methods used for polymer processing is the use of supercritical carbon dioxide (scCO2) since it has mass-transfer properties adapted to the foam morphology, generating different path lengths for the diffusion of active compounds within its structure and can dissolve a wide range of organic molecules under supercritical conditions. The objective of this research was to evaluate the effect of operational variables on the process of caffeic acid (CA) impregnation and subsequent foaming of polylactic acid (PLA) as well as two PLA/poly(butylene-co-terephthalate-adipate) (PBAT) blends using scCO2. The results showed an increase in the degree of crystallinity of the CA-impregnated samples due to the nucleation effect of the active compound. On the other hand, SEM micrographs of both films and foams showed significant differences due to the presence of PBAT and its low miscibility with PLA. Finally, the results obtained in this work contribute to the knowledge of the important parameters to consider for the implementation of the impregnation and foaming process of PLA and PLA/PBAT blends with potential use in food packaging. © 2024 by the authors.